A Physiological Perspective on Lactation in Goats: A Review - SALUM, Çağatay; ETYEMEZ, Muhammed (Department of Veterinary Sciences, Yozgat Bozok University, 2023)
The domesticated species of goats, scientifically known as Capra hircus, have played a significant role in several aspects of human existence over the course of history. These animals have made notable contributions to both individual animal breeding practices and the overall national economy. Their unique meat and milk production, along with their ease of cultivation, distinguish them as noteworthy entities. Goat milk is widely favored by customers due to its hypoallergenic features, low lactose levels, and rich composition. As a result, goat breeding has been prevalent in our country and globally for milk production in animal husbandry. In accordance with the purpose of achieving a high-quality final product, which constitutes a primary goal of animal husbandry, it is important to possess knowledge on certain attributes relating to the animal under cultivation. The aforementioned characteristics pertain to the anatomical composition of the udder and the physiological processes involved in breastfeeding in goats. Lactation physiology encompasses three key processes: mammogenesis, lactogenesis, and galactopoiesis. Mammogenesis refers to the formation of the udder, while lactogenesis involves the secretion of milk. Galactopoiesis, on the other hand, pertains to the maintenance of continuous milk supply. This review will examine the reproductive cycle, physical structure, and developmental aspects of the udder, as well as the many stages of lactation physiology in goats.
Keywords: Galaktopoez; Keçi; Keçi Sütü; Laktasyon Fizyolojisi; Mammogenez; Galactopoiesis; Goat; Goat Milk; Lactation Physiology; Mammogenesis; Veterinary Sciences (Other); Veteriner Bilimleri (Diğer); 2. Zero hunger